An incised shell object from Baradostian (Early Upper Palaeolithic) layers in Shanidar Cave, Iraqi Kurdistan. (August 2017) - Hunt, Chris O.; Hill, Evan A.; Reynolds, Tim; Abdulmutalb, Dlshad; Farr, Lucy; Lane, Ross; Szabó, Katherine; Barker, Graeme
Abstract: Shanidar Cave contains one of the most important Palaeolithic archaeological sequences in West Asia. During renewed excavations of Baradostian (Upper Palaeolithic) layers in the cave, an incised land-snail shell fragment was recovered. A natural cause seems unlikely and it does not appear likely to reflect palaeoeconomic functions. It is suggested tentatively that this may have been made during manufacture of a composite artefact designed for visual display. Although Upper Palaeolithic ornaments are often reported, composite ornaments of this period are rather unusual. Highlights: An incised shell fragment from the Upper Palaeolithic of Shanidar Cave Baradostian – Upper Palaeolithic - equivalent to the Aurignacian Natural causes or subsistence activity unlikely Possibly from manufacture of multi-component item for visual display